2013, Nr. 13, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Accounting and auditing challengesJonas Mackevičius, Jonas Martinavičius, Lionius Gaižauskas, The analysis of accounting and audit specialists release and their satisfaction with studies at Vilnius University (1990-2012), 7Dovilė Latakaitė, Kristina Rudžionienė, Corporate social responsibility information disclosure in the financial reports, 21Lukas Giriūnas, Evaluation of the determinants of fraud and errors, 32Светлана Бычкова, Елeна Итыгилова, Institutional substantiation of the concept of responsibility in auditing: philosophical, sociological and economic aspects, 40Lionius Gaižauskas, Jonas Martinavičius, Budgetary control challenges in Lithuanian companies, 50Problems of financial markets and economicsInese Vigante, Ruta Sneidere, Problematic aspects of the VAT Reverse charge arrangements, 63Arvydas Paškevičius, Clients of equity-index lined bonds: risk assessment, 79Valentina  Bogatyrova, The efficiency increase problems in the Belarussian economy: financial management of human capital, 96Marija Kučinskienė, Dainius Baliūnas, Environment influence assessment to inflections of structural changes, 109Elena Kurlavičiūtė, The comparative analysis of Lithuanian and Finland expenditure on public goods, 117
Keywords: none